Composite material and preparation method thereof, photoelectric device and display device

Through the composite material of inorganic P-type semiconductor particles and fluorine-containing lithium salt, the problem of unbalanced electron and hole injection in optoelectronic devices is solved, hole mobility and device performance are improved, and efficient carrier transmission and stability are achieved.

CN120247106APending Publication Date: 2025-07-04SHENZHEN TCL HIGH TECH DEVELOPMENT CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311864219.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-29
Publication Date
2025-07-04

AI Technical Summary

Technical Problem

In existing optoelectronic devices, the unbalanced electron and hole injection leads to poor performance and low carrier mobility efficiency, which affects the device's photoelectric performance and stability.

Method used

Inorganic P-type semiconductor particles and fluorine-containing lithium salt composite materials are used to improve hole transmission efficiency through the conductivity of lithium ions and the electronegativity of fluorine atoms, and passivate the defects of inorganic P-type semiconductor particles to form an efficient hole functional layer.

Benefits of technology

It improves hole mobility, reduces interface loss and leakage current, and enhances the external quantum efficiency and service life of optoelectronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120247106A_ABST
    Figure CN120247106A_ABST
Patent Text Reader

Abstract

The invention discloses a composite material and a preparation method thereof, a photoelectric device and a display device, and relates to the technical field of display. The composite material comprises inorganic P-type semiconductor particles and fluorine-containing lithium salt. The composite material provided by the invention is high in hole migration efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of display technologies, and in particular, to a composite material, a preparation method thereof, an optoelectronic device, and a display device. Background Art

[0002] Currently, the widely used optoelectronic devices are organic light-emitting diodes (OLEDs) and quantum dot light-emitting diodes (QLEDs). Due to their excellent display performance such as self-luminescence, simple structure, ultra-thinness, fast response speed, wide viewing angle, low power consumption, and flexible display, OLEDs have become the mainstream technology in the field of display technologies. QLEDs have the advantages of saturated emission light color and adjustable wavelength, and high photoluminescence and electroluminescence quantum yields. In recent years, they have become strong competitors of OLEDs.

[0003] The structures of traditional OLED and QLED devices generally include an anode, a hole injection layer, a hole transport layer, a light-emitting layer, an electron transport layer, an electron injection layer, and a cathode. Under the action of an electric field, the holes generated by the anode and the electrons generated by the cathode of the light-emitting diode move, are respectively injected into the hole transport layer and the electron transport layer, and finally migrate to the light-emitting layer. When the two meet in the light-emitting layer, energy excitons are generated, thereby exciting the light-emitting molecules to finally generate visible light.

[0004] The carrier migration efficiency of existing carrier functional materials is relatively low and needs to be further improved. Summary of the Invention

[0005] In view of this, the present application provides a composite material, a preparation method thereof, an optoelectronic device, and a display device.

[0006] An embodiment of the present application is implemented as follows. A composite material includes inorganic P-type semiconductor particles and a fluorinated lithium salt.

[0007] Correspondingly, an embodiment of the present application further provides a preparation method of a composite material, including:

[0008] Providing a dispersion liquid of inorganic P-type semiconductor particles, where the dispersion liquid of inorganic P-type semiconductor particles includes inorganic P-type semiconductor particles;

[0009] Providing a fluorinated lithium salt, and mixing the fluorinated lithium salt and the dispersion liquid of inorganic P-type semiconductor particles to obtain a composite material.

[0010] Correspondingly, an embodiment of the present application further provides an optoelectronic device, including an anode, a hole functional layer, an active layer, and a cathode that are sequentially stacked; the material of the hole functional layer includes the above composite material, or includes the composite material prepared by the above preparation method.

[0011] Correspondingly, an embodiment of the present application further provides a display device, and the display device includes the above-mentioned optoelectronic device.

[0012] The composite material provided by the present application has high hole migration efficiency. Description of the Drawings

[0013] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the following will briefly introduce the drawings required for the description of the embodiments. Obviously, the drawings in the following description are only some embodiments of the present application. For those skilled in the art, without creative efforts, other drawings can be obtained based on these drawings.

[0014] Figure 1 is a flowchart of a method for preparing the composite material provided by an embodiment of the present application;

[0015] Figure 2 is a schematic structural diagram of an optoelectronic device provided by an embodiment of the present application;

[0016] Figure 3 is a schematic structural diagram of another optoelectronic device provided by an embodiment of the present application.

[0017] Reference Signs:

[0018] Anode 10; Hole functional layer 20; Hole injection layer 21; Hole transport layer 22; Active layer 30; Cathode 40; Electron functional layer 50. Detailed Embodiments

[0019] The following will clearly and completely describe the technical solutions in the embodiments of the present application with reference to the drawings in the embodiments of the present application. Obviously, the described embodiments are only some embodiments of the present application, rather than all embodiments. Based on the embodiments of the present application, all other embodiments obtained by those skilled in the art without creative efforts belong to the scope of protection of the present application. In addition, it should be understood that the specific embodiments described herein are only used to illustrate and explain the present application, and are not used to limit the present application.

[0020] In the present application, unless otherwise stated, the orientation terms such as "upper" and "lower" usually refer to the upper and lower in the actual use or working state of the device, specifically the drawing direction in the drawings; and "inner" and "outer" refer to the outline of the device. In addition, in the description of the present application, the term "comprising" means "including but not limited to". The terms first, second, third, etc. are only used as labels and do not impose numerical requirements or establish an order.

[0021] In this application, "and / or" describes the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist simultaneously, or B exists alone. Here, A and B can be singular or plural.

[0022] In this application, "at least one" means one or more, and "a plurality" means two or more. "One or several", "at least one (item) below" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one (item) among a, b, or c", or "at least one (item) among a, b, and c" can both represent: a, b, c, a - b (i.e., a and b), a - c, b - c, or a - b - c, where a, b, and c can be single or multiple respectively.

[0023] The various embodiments of this application can exist in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be construed as a rigid limitation on the scope of this application; therefore, it should be considered that the described range description has specifically disclosed all possible sub - ranges and individual values within that range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub - ranges such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., and individual numbers within the range, such as 1, 2, 3, 4, 5, and 6, and this applies regardless of the range. Additionally, whenever a numerical range is indicated herein, it means including any cited number (fraction or integer) within the indicated range.

[0024] In existing optoelectronic devices, the imbalance between electron and hole injection leads to poor performance of optoelectronic devices. The imbalance between electrons and holes is mainly due to the following reasons: on the one hand, the mobility of P - type hole - transporting materials is much smaller than that of N - type electron - transporting materials; on the other hand, the interfacial energy - level barrier between the hole - functional layer and the light - emitting layer is greater than the interfacial potential barrier between the electron - functional layer and the light - emitting layer, making hole injection more difficult. Most of the currently used quantum - dot light - emitting materials are cadmium - based quantum dots. Most cadmium - based quantum dots have a relatively deep valence - band maximum (VBM, - 6 eV to - 7 eV), while the highest occupied molecular orbital (HOMO) energy levels of most hole - functional materials are relatively shallow. This difference results in an overly large hole - injection barrier; the conduction band of cadmium - based quantum dots is approximately at - 4.0 eV, which is basically consistent with the lowest unoccupied molecular orbital (LUMO) energy level of electron - functional materials, making electron injection easier than hole injection. The imbalance between electrons and holes hinders the improvement of the optoelectronic performance of optoelectronic devices, and the excessive accumulation of electrons will also increase the probability of non - radiative recombination, causing exciton quenching and reducing the stability and lifespan of optoelectronic devices.

[0025] At present, some inorganic particles are used in the materials of the hole functional layer, such as nickel oxide (NiO), etc. As an inorganic P-type semiconductor particle, nickel oxide has a relatively matched band gap (band gap of 3.8 eV, HOMO energy level of -5.4 eV, LUMO energy level of -1.6 eV), and has high light transmittance in the ultraviolet region, visible light region and near-infrared light region, excellent chemical stability and unique optical, electrical and magnetic properties, etc., and is widely used in electrochromic devices, organic light-emitting diodes, gas sensors, dye-sensitized solar cells and p-n heterojunctions. The crystal structure of nickel oxide belongs to the NaCl type, with a face-centered cubic crystal form, lattice constant (a = b = c = 0.416 nm), and the band gap at room temperature is 3.6 eV - 4.0 eV. Although there are an odd number of valence electrons in a nickel oxide unit cell, according to the band theory, it should have good conductivity. However, due to the mutual quantum entanglement between electrons, a completely pure intrinsic nickel oxide crystal is a Mohs insulator, and the resistivity at room temperature is 1013 Ω·cm. Therefore, there are great application bottlenecks in its application as a hole functional layer in optoelectronic devices. The large resistance will cause a large electric field strength and voltage drop in the nickel oxide layer of the device, not only generating a large amount of Joule heat but also increasing the turn-on voltage of the device, reducing the hole injection efficiency, current efficiency and service life of the device; due to the very low carrier concentration and carrier mobility of intrinsic nickel oxide, it will also lead to unbalanced carrier transport in the device and form a large leakage current, the quantum dots are severely charged and the carrier recombination region crosses the quantum dot light-emitting layer and approaches the anode, resulting in a very low external quantum efficiency of the device.

[0026] The technical solution of this application is as follows:

[0027] In the first aspect, an embodiment of this application provides a composite material, including an inorganic P-type semiconductor particle and a fluorinated lithium salt.

[0028] The composite material provided by this application includes an inorganic P-type semiconductor particle and a fluorinated lithium salt. In the fluorinated lithium salt, lithium ions have good conductivity and a relatively small ionic radius, are easy to move, and can effectively transfer holes, improving the conductivity of the thin film and reducing interface loss; the presence of fluoride ions can form covalent bonds with the inorganic P-type semiconductor particles to passivate the defects of the inorganic P-type semiconductor particles, inhibit non-radiative relaxation of carriers, and improve the effective transport of holes; in addition, the large electronegativity of fluorine atoms ensures that the electron affinity is large enough, and the ability to attract electrons is stronger. Therefore, when it combines with the inorganic P-type semiconductor particles, electrons will tend to the side of fluorine atoms to form a dipole with a greater polarity of the material, which can strengthen the flow of holes inside it to a certain extent and increase the hole transport efficiency of the composite material.

[0029] In some embodiments, the inorganic P-type semiconductor particles include one or more of first doped metal oxide particles, first undoped metal oxide particles, metal sulfides, metal selenides, and metal nitrides. The metal oxides in the first doped metal oxide particles and the metal oxides in the first undoped metal oxide particles independently include one or more of MoO3, WO3, NiO, CrO3, CuO, and V2O5. The doping elements in the first doped metal oxide particles include one or more of Mo, W, Ni, Cr, Cu, and V. The metal sulfides include one or more of CuS, MoS3, and WS3. The metal selenides include one or more of MoSe3 and WSe3. The metal nitrides include p-type gallium nitride.

[0030] Exemplarily, when the inorganic P-type semiconductor particles are NiO, Ni in NiO can form Ni-F ionic bonds with F in the fluorinated lithium salt, thereby passivating the interstitial nickel defects.

[0031] In some embodiments, the inorganic P-type semiconductor particles contain oxygen elements. For example, the inorganic P-type semiconductor particles are one or more of the first doped metal oxide particles and the first undoped metal oxide particles among the above inorganic P-type semiconductor particles. It can be understood that the ionic radius of fluoride ions is very close to that of oxygen ions, so it can make up for the lack of oxygen vacancies and passivate oxygen vacancy defects. And the electronegativity of fluorine atoms is 4.0, while the electronegativity of oxygen atoms is 3.5. Fluorine atoms can better fill the vacancies of oxygen atoms and tightly bind to the crystal of the inorganic P-type semiconductor particles, maintaining and strengthening the stability of the crystal of the inorganic P-type semiconductor particles.

[0032] In some embodiments, the average particle size of the inorganic P-type semiconductor particles is 5 nm to 10 nm, and can be, for example, 6 nm, 7 nm, 8 nm, 9 nm, etc.

[0033] In some embodiments, the fluorinated lithium salt includes one or more of inorganic fluorinated lithium salts and organic fluorinated lithium salts.

[0034] Further, the inorganic fluorinated lithium salts include one or more of lithium fluoride, lithium fluorophosphate salts, lithium fluoroborate salts, and lithium fluorosilicate salts.

[0035] The lithium fluorophosphate salts include one or more of lithium hexafluorophosphate and lithium difluorophosphate.

[0036] The lithium fluoroborate salt includes lithium tetrafluoroborate.

[0037] The lithium fluorosilicate salt includes lithium hexafluorosilicate.

[0038] The organic fluorine-containing lithium salt includes one or more of lithium fluorosulfonimide salt, lithium fluoroxalate borate, and lithium fluorosulfonate.

[0039] The lithium fluorosulfonimide salt includes one or more of lithium bis(trifluoromethylsulfonyl)imide, lithium trifluoromethanesulfonimide, and lithium bis(fluorosulfonyl)imide.

[0040] The lithium borate salt includes lithium difluorooxalate borate.

[0041] The lithium fluorosulfonate salt includes one or more of lithium nonafluoro-1-butanesulfonate and lithium trifluoromethanesulfonate.

[0042] In some embodiments, in the composite material, the mass ratio of the inorganic P-type semiconductor particles to the fluorine-containing lithium salt is (10-20):1, and for example, it can be 11:1, 12:1, 13:1, 14:1, 15:1, 16:1, 17:1, 18:1, 19:1, etc. Within the range of the mass ratio, it is beneficial for the fluorine-containing lithium salt to effectively improve the hole mobility of the inorganic P-type semiconductor particles.

[0043] In some embodiments, in the composite material, the inorganic P-type semiconductor particles contain metal cations, the fluorine-containing lithium salt contains fluoride ions, and the metal cations and the fluoride ions are connected by ionic bonds.

[0044] In some embodiments, the inorganic P-type semiconductor particles contain anion vacancy defects, and the fluoride ions in the fluorine-containing lithium salt fill the anion vacancy defects.

[0045] In some embodiments, the composite material is composed of the inorganic P-type semiconductor particles and the fluorine-containing lithium salt.

[0046] In a second aspect, please refer to Figure 1 , the embodiments of the present application further provide a preparation method of a composite material, including:

[0047] S11. Provide an inorganic P-type semiconductor particle dispersion liquid, and the inorganic P-type semiconductor particle dispersion liquid includes inorganic P-type semiconductor particles;

[0048] S12. Provide a fluorine-containing lithium salt, and mix the fluorine-containing lithium salt and the inorganic P-type semiconductor particle dispersion liquid to obtain a composite material.

[0049] The inorganic P-type semiconductor particles and the fluorine-containing lithium salt are as described above, and will not be elaborated here.

[0050] In S11:

[0051] In some embodiments, in the inorganic P-type semiconductor particle dispersion liquid, the mass concentration of the inorganic P-type semiconductor particles is 10 mg / mL to 40 mg / mL, and can be, for example, 15 mg / mL, 20 mg / mL, 25 mg / mL, 30 mg / mL, 35 mg / mL, etc. Within the range of the mass concentration, it is beneficial to the dissolution and dispersion of the inorganic P-type semiconductor particles.

[0052] In some embodiments, the inorganic P-type semiconductor particle dispersion liquid further includes a solvent.

[0053] Further, the solvent includes one or more of chlorobenzene, diethylene glycol monobutyl ether, trimethoxybutanol, triethylene glycol monobutyl ether, diethylene glycol dimethyl ether, methanol, ethanol, propanol, butanol, ethylene glycol, isopropanol, glycerol, dimethyl sulfoxide, acetone, acetophenone, tetrahydrofuran, N,N-dimethylformamide, ethyl acetate, pyrrole, butyric acid, and cresol.

[0054] In the step S12:

[0055] It can be understood that the inorganic P-type semiconductor particles can be prepared by conventional preparation methods in the art, such as the solution method.

[0056] In some embodiments, the mass ratio of the inorganic P-type semiconductor particles to the fluorinated lithium salt is (10 to 20):1, and can be, for example, 11:1, 12:1, 13:1, 14:1, 15:1, 16:1, 17:1, 18:1, 19:1, etc. Within the range of the mass ratio, it is beneficial for the fluorinated lithium salt and the inorganic P-type semiconductor particles to come into full contact and react.

[0057] In some embodiments, after the fluorinated lithium salt and the inorganic P-type semiconductor particle dispersion liquid are mixed, heating is further included.

[0058] In some embodiments, the temperature of the heating is 150 °C to 200 °C, and can be, for example, 155 °C, 160 °C, 165 °C, 170 °C, 175 °C, 180 °C, 185 °C, 190 °C, etc.; the time of the heating is 12 h to 18 h, and can be, for example, 13 h, 14 h, 15 h, 16 h, 17 h, etc.

[0059] In this way, it is beneficial to improve the reaction yield of the fluorinated lithium salt and the inorganic P-type semiconductor particles.

[0060] In some embodiments, after the heating, separation and drying are further included.

[0061] Further, the separation method can be centrifugation, and the rotation speed of the centrifugation is 2000 rpm to 5000 rpm, for example, it can be 2500 rpm, 3000 rpm, 3500 rpm, 4000 rpm, 4500 rpm, etc.; the centrifugation time is 1 min to 10 min. In this way, it is beneficial to remove the solvent and obtain the composite material in the precipitate.

[0062] In some embodiments, after the separation and before the drying, washing is further included.

[0063] Further, the washing reagent is one or more of deionized water, absolute ethanol, chloroform, and acetone; the number of washing times is 3 to 5 times. In this way, it is beneficial to wash away the residual solvent on the surface of the composite material and improve the purity of the composite material.

[0064] In some embodiments, the drying includes natural drying, heating drying, vacuum drying, etc. Further, the temperature of the heating drying is 100°C to 120°C, for example, it can be 102°C, 105°C, 108°C, 110°C, 112°C, 115°C, 118°C, etc.; the heating drying time is 5 h to 8 h, for example, it can be 5.5 h, 6 h, 6.5 h, 7 h, 7.5 h, etc. In this way, it is beneficial to remove the washing reagent and obtain a high-performance composite material.

[0065] The preparation method of the composite material provided by this application is simple in operation and low in cost, and can effectively prepare the composite material.

[0066] In the third aspect, please refer to Figure 2 , this application embodiment also provides an optoelectronic device, which includes an anode 10, a hole functional layer 20, an active layer 30, and a cathode 40 stacked in sequence; the material of the hole functional layer 20 includes the above composite material.

[0067] In the optoelectronic device provided by this application, the material of the hole functional layer 20 includes inorganic P-type semiconductor particles and fluorinated lithium salts; the inorganic P-type semiconductor particles have more defects, which will cause their instability during the film-forming process and easily lead to agglomeration, resulting in unevenness of the film and affecting the contact resistance between the interface layers. The addition of fluorinated lithium salts can better alleviate the occurrence of this situation; lithium ions have good conductivity and small ionic radii, which are convenient for movement and can effectively transfer holes between the hole functional layer 20 and the active layer 30, improving the conductivity of the hole functional layer 20 and reducing the interface loss. The fluoride ions in the fluorinated lithium salts can also passivate the defects of the inorganic P-type semiconductor particles, making the hole functional layer 20 flatter, greatly reducing the contact resistance between the interfaces, and reducing the leakage current of the optoelectronic device; inhibiting the non-radiative relaxation of carriers between the interfaces, while improving the effective transmission of charges between the interfaces, thereby improving the lifetime and performance of the device.

[0068] It can be understood that the optoelectronic device provided by the present application can be a front-mounted optoelectronic device or an inverted optoelectronic device.

[0069] Please refer to Figure 3 , in some embodiments, the hole functional layer 20 includes one or more of a hole injection layer 21 and a hole transport layer 22.

[0070] In some embodiments, the optoelectronic device further includes an electron functional layer 50, and the electron functional layer 50 is disposed between the active layer 30 and the cathode 40.

[0071] Further, the electron functional layer 50 includes one or more of an electron injection layer and an electron transport layer.

[0072] In some embodiments, the material of the electron functional layer 50 includes one or more of second doped metal oxide particles, second undoped metal oxide particles, IIB-VIA group inorganic particles, IIIA-VA group inorganic particles, and IB-IIIA-VIA group inorganic particles. The material of the second undoped metal oxide particles includes one or more of ZnO, TiO2, SnO2, ZrO2, and Ta2O5. The metal oxides in the second doped metal oxide particles include one or more of ZnO, TiO2, SnO2, ZrO2, Ta2O5, and Al2O3. The doping elements in the second doped metal oxide particles include one or more of Al, Mg, Li, Mn, Y, La, Cu, Ni, Zr, Ce, In, and Ga. The IIB-VIA group inorganic particles include one or more of ZnS, ZnSe, and CdS. The IIIA-VA group inorganic particles include one or more of InP and GaP. The IB-IIIA-VIA group inorganic particles include one or more of CuInS and CuGaS.

[0073] In some embodiments, the optoelectronic device includes a light-emitting diode. The active layer 30 includes a light-emitting layer.

[0074] In some embodiments, the anode 10 and the cathode 40 each independently include one or more of a metal, a carbon material, and a metal oxide; the metal includes one or more of Al, Ag, Cu, Mo, Au, Ba, Ca, Yb, and Mg; the carbon material includes one or more of graphite, carbon nanotubes, graphene, and carbon fiber; the metal oxide includes a metal oxide electrode or a composite electrode with a metal disposed between doped or undoped transparent metal oxides. The material of the metal oxide electrode includes one or more of ITO, FTO, ATO, AZO, GZO, IZO, MZO, MoO3, and AMO. The composite electrode includes one or more of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, ZnS / Ag / ZnS, ZnS / Al / ZnS, TiO2 / Ag / TiO2, and TiO2 / Al / TiO2. Herein, " / " represents a laminated structure. For example, AZO / Ag / AZO represents a composite electrode including an AZO layer, an Ag layer, and an AZO layer laminated in sequence.

[0075] In some embodiments, the material of the active layer 30 includes a light-emitting material, and the light-emitting material includes one or more of an organic light-emitting material and a quantum dot light-emitting material.

[0076] The organic light-emitting material can be selected from, but not limited to, one or more of CBP:Ir(mppy)3 (4,4'-bis(N-carbazolyl)-1,1'-biphenyl: tris[2-(p-tolyl)pyridine iridium(III)]), TCTX:Ir(mmpy) (4,4',4”-tris(carbazol-9-yl)triphenylamine: tris[2-(p-tolyl)pyridine iridium]), diaryl anthracene derivatives, stilbene aromatic derivatives, pyrene derivatives, fluorene derivatives, TBPe fluorescent material, TTPX fluorescent material, TBRb fluorescent material, DBP fluorescent material, delayed fluorescence material, TTA material, TADF (thermally activated delayed) material, polymer containing B-N covalent bond, HLCT (hybrid local charge transfer excited state) material, and Exciplex (excimer complex) light-emitting material.

[0077] The quantum dot light-emitting material can be selected from, but not limited to, one or more of single-structure quantum dots, core-shell structure quantum dots, and perovskite-type inorganic particles.

[0078] The material of the single-structure quantum dots, the core material of the core-shell structure quantum dots, and the shell material of the core-shell structure quantum dots can be respectively selected from one or more of II-VI group compounds, IV-VI group compounds, III-V group compounds, and I-III-VI group compounds. The shell of the core-shell structure quantum dots is one or more layers. The II-VI group compounds can be selected from, but not limited to, one or more of CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe, and HgZnSTe. The IV-VI group compounds can be selected from, but not limited to, one or more of SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, and SnPbSTe. The III-V group compounds can be selected from, but not limited to, one or more of GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs, and InAlPSb. The I-III-VI group compounds can be selected from, but not limited to, one or more of CuInS2, CuInSe2, and AgInS2.

[0079] As an example, the quantum dots of the core-shell structure can be selected from but not limited to one or more of CdSe / CdSeS / CdS, InP / ZnSeS / ZnS, CdZnSe / ZnSe / ZnS, CdSeS / ZnSeS / ZnS, CdSe / ZnS, CdSe / ZnSe / ZnS, ZnSe / ZnS, ZnSeTe / ZnS, CdSe / CdZnSeS / ZnS, and InP / ZnSe / ZnS. In the expressions such as CdSe / ZnS above, the " / " indicates that the material after " / " (as the shell layer) coats the material before " / " (as the core layer).

[0080] The perovskite-type inorganic particles can be selected from but not limited to doped or undoped inorganic perovskite-type semiconductors, or organic-inorganic hybrid perovskite-type semiconductors. The general structural formula of the inorganic perovskite-type semiconductor is AMX3, where A is a Cs + ion, M is a divalent metal cation selected from 2+ Pb 2+ Sn 2+ Cu 2+ Ni 2+ Cd 2+ Cr 2+ Mn 2+ Co 2+ Fe 2+ Ge 2+ Yb 2+ Eu - Cl - Br - I n-2 NH3 + or [NH3(CH2) n NH3] 2+ where n≥2, M is a divalent metal cation selected from 2+ Pb 2+ Sn 2+ Cu 2+ Ni 2+ Cd 2+ Cr 2+ Mn 2+ Co 2+ Fe 2+ Ge 2+ Yb 2+ Eu - Cl - Br -One or more of the above.

[0081] In a fourth aspect, an embodiment of the present application further provides a display device, and the display device includes the above optoelectronic device.

[0082] The display device may be any electronic product with a display function, and the electronic product includes but is not limited to a smart phone, a tablet computer, a laptop computer, a digital camera, a digital video camera, a smart wearable device, a smart weighing electronic scale, a vehicle-mounted display, a television, or an e-book reader. Among them, the smart wearable device may be, for example, a smart bracelet, a smart watch, a virtual reality (VR) helmet, etc.

[0083] The present application will be specifically described below through specific embodiments. The following embodiments are only partial embodiments of the present application and do not limit the present application.

[0084] Embodiment 1

[0085] This embodiment provides a composite material, including inorganic P-type semiconductor particles NiO and lithium hexafluorophosphate. The mass ratio of NiO to lithium hexafluorophosphate is 10:1. The preparation method is as follows:

[0086] Weigh 240 mg of NiO and dissolve it in 10 mL of butanol to prepare a solution with a concentration of 24 mg / mL. Then add 16 mg of lithium hexafluorophosphate thereto, and then transfer it to a 50 mL polytetrafluoroethylene reaction kettle. Carry out a solvothermal reaction at 180 °C for 36 h in a forced-air drying oven, then naturally cool to room temperature, centrifuge and separate the precipitate, wash it 4 times with deionized water and anhydrous ethanol respectively, and finally dry it at 110 °C for 6 h to obtain the composite material.

[0087] Embodiment 2

[0088] Embodiment 2 is basically the same as Embodiment 1, except that the mass of lithium hexafluorophosphate in Embodiment 2 is 24 mg.

[0089] Embodiment 3

[0090] Embodiment 3 is basically the same as Embodiment 1, except that the mass of lithium hexafluorophosphate in Embodiment 3 is 12 mg.

[0091] Embodiment 4

[0092] Embodiment 4 is basically the same as Embodiment 1, except that the reaction temperature of NiO and lithium hexafluorophosphate in Embodiment 4 is 200 °C.

[0093] Embodiment 5

[0094] Example 5 is basically the same as Example 1, except that in Example 5, the reaction temperature of NiO and lithium hexafluorophosphate is 150 °C.

[0095] Example 6

[0096] Example 6 is basically the same as Example 1, except that in Example 6, the reaction time of NiO and lithium hexafluorophosphate is 48 h.

[0097] Example 7

[0098] Example 7 is basically the same as Example 1, except that in Example 7, the reaction time of NiO and lithium hexafluorophosphate is 12 h.

[0099] Example 8

[0100] Example 8 is basically the same as Example 1, except that in Example 8, NiO is replaced with CuO.

[0101] Example 9

[0102] Example 9 is basically the same as Example 1, except that in Example 9, NiO is replaced with V2O5.

[0103] Example 10

[0104] Example 10 is basically the same as Example 1, except that in Example 10, lithium hexafluorophosphate is replaced with lithium fluoride.

[0105] Example 11

[0106] Example 11 is basically the same as Example 1, except that in Example 11, lithium hexafluorophosphate is replaced with lithium nonafluoro-1-butanesulfonate.

[0107] Comparative Example 1

[0108] This comparative example provides a material including inorganic P-type semiconductor particles NiO.

[0109] Comparative Example 2

[0110] This comparative example provides a material including inorganic P-type semiconductor particles CuO.

[0111] Comparative Example 3

[0112] This comparative example provides a material including inorganic P-type semiconductor particles V2O5.

[0113] The hole mobilities of the composite materials of Examples 1 to 11 and the material of Comparative Example 1 were tested respectively, and the results are shown in Table 1.

[0114] Among them, the test method for hole mobility is as follows: measure the current density-voltage curve of the half-device (single-carrier transport thin-film device HOD) of the optoelectronic device. The structure of the HOD is anode / hole transport thin film / quantum dot light-emitting layer / cathode. Obtain the space charge limited current (SCLC) region in the current density-voltage curve, and then according to the formula J=(9 / 8)ε r ε0μ e V 2 / d 3 calculate the hole mobility. Among them, J represents the current density, and the unit is mAcm -2 ; ε r represents the relative dielectric constant; ε0 represents the vacuum dielectric constant; μ e represents the hole mobility, and the unit is cm 2 V -1 s -1 ; V represents the driving voltage, and the unit is V; d represents the film thickness, and the unit is m.

[0115] Table 1

[0116]

[0117] As can be seen from Table 1:

[0118] From Examples 1 to 3 and Comparative Example 1, it can be obtained that adding a fluorinated lithium salt to the inorganic P-type semiconductor particles can effectively improve the hole mobility of the inorganic P-type semiconductor particles. Especially within the range of the mass ratio of the inorganic P-type semiconductor particles and the fluorinated lithium salt provided in this application, when the mass ratio of the inorganic P-type semiconductor particles and the fluorinated lithium salt is moderate, the hole mobility is relatively high;

[0119] From Examples 1, 4 to 7 and Comparative Example 1, it can be obtained that within the range provided in this application, the temperature and time of the mixing reaction of the inorganic P-type semiconductor particles and the fluorinated lithium salt have little effect on the hole mobility of the composite material. The hole mobilities of the composite materials in Examples 4 to 7 are much higher than those of the composite material in Comparative Example 1;

[0120] From Examples 1, 8 to 11 and Comparative Examples 1 to 3, it can be obtained that different fluorinated lithium salts have a great influence on the hole mobility of the composite material. Among lithium hexafluorophosphate, lithium fluoride and lithium nonafluoro-1-butanesulfonate, lithium hexafluorophosphate has the best improvement effect on the inorganic P-type semiconductor particles, and the hole mobility is relatively the highest; different inorganic P-type semiconductor particles will also affect the hole mobility of the composite material, which is related to the properties of the inorganic P-type semiconductor particles themselves. Compared with the composite materials of Comparative Examples 1 to 3 corresponding to the composite materials of Examples 1, 8 to 9, the hole mobilities have all been significantly improved.

[0121] Device Example 1

[0122] This embodiment provides an optoelectronic device, and the preparation method is as follows:

[0123] First, clean the ITO conductive glass. Dip a cotton swab in a small amount of soapy water and wipe the ITO surface to remove visible impurities on the surface. Then, ultrasonically clean it with deionized water, acetone, ethanol, and isopropanol for 15 min, and then dry it with nitrogen for later use to form the anode;

[0124] Use a pipette to suck 50 μL of the prepared PEDOT:PSS solution and drop it on the ITO. Then start spin coating. The spin coating speed is 4000 rpm, and the time is controlled within 50 seconds. Then perform annealing. The annealing temperature is 150 °C, and the annealing time is controlled within 15 min to form the hole injection layer;

[0125] Dissolve the composite material of Example 1 in ethanol to prepare a dispersion of 10 mg / mL. Suck 40 μL of the composite material of Example 1 and slowly drop it on top of the hole injection layer, and then perform spin coating. The spin coating speed is 4000 rpm, and the time is controlled within 30 s. Then perform annealing. The annealing temperature is 140 °C, and the annealing time is controlled within 15 min to form the hole transport layer;

[0126] Dissolve the prepared CdZnS quantum dots in n - hexane to obtain a quantum dot solution with a concentration of 15 mg / mL. Use a pipette to suck 40 μL and drop it on the surface already containing the hole transport layer, and then perform spin coating. The spin coating speed is 3000 rpm, and the time is controlled within 40 s. Then perform annealing. The annealing temperature is 120 °C, and the annealing time is controlled within 10 min to form the light - emitting layer;

[0127] Use a pipette to suck 40 μL of zinc oxide solution and slowly drop it on top of the light - emitting layer, and then perform spin coating. The spin coating speed is 4000 rpm, and the time is controlled within 30 s. Then perform annealing. The annealing temperature is 130 °C, and the annealing time is controlled within 15 min to form the electron transport layer;

[0128] Perform electrode evaporation. Put the above - mentioned device into a vacuum coating machine and pump the vacuum to 4×10 -6 mbar. When evaporating, first evaporate the magnesium target. The magnesium target is evaporated at a rate to a thickness of 15 nm; then turn on the Ag target. The Ag target is evaporated at a rate to a thickness of 30 nm;

[0129] Encapsulate with ultraviolet - curable glue to obtain the optoelectronic device.

[0130] Device Examples 2 - 11

[0131] Device Examples 2 to 11 are basically the same as Device Example 1, except that in Device Examples 2 to 11, the composite material of Example 1 is respectively replaced by the composite materials of Examples 2 to 11.

[0132] Device Comparative Examples 1 to 3

[0133] Device Comparative Examples 1 to 3 are basically the same as Device Example 1, except that in Device Comparative Examples 1 to 3, the composite material of Example 1 is respectively replaced by the materials of Comparative Examples 1 to 3.

[0134] The leakage current, external quantum efficiency EQE, and lifetime T95@1000nit of the optoelectronic devices of Device Examples 1 to 11 and Device Comparative Examples 1 to 3 were respectively tested, and the results are shown in Table 2.

[0135] Among them, the test method for leakage current is as follows: the corresponding voltage, current, and brightness are measured by an efficiency test system built with Keithley 2400 and Keithley 6485, and the leakage current can be obtained from the brightness-current curve.

[0136] The test method for the external quantum efficiency EQE is as follows: the ratio of the number of electron-hole pairs injected into the quantum dots to the number of emitted photons, with the unit of %, is an important parameter to measure the quality of electroluminescent devices, and it can be obtained by measuring with an EQE optical test instrument. The specific calculation formula is as follows:

[0137]

[0138] Among them, ηe is the optical output coupling efficiency, ηr is the ratio of the number of recombined carriers to the number of injected carriers, χ is the ratio of the number of excitons generating photons to the total number of excitons, K R is the radiation process rate, and K NR is the non-radiation process rate.

[0139] Test conditions: carried out at room temperature, with the air humidity of 30 - 60%.

[0140] The test method for the lifetime T95@1000nit is as follows: the time required for the brightness of the device to decrease to a certain proportion of the highest brightness under constant current or voltage drive. The time when the brightness drops to 95% of the highest brightness is defined as T95, and this lifetime is the measured lifetime. To shorten the test cycle, the device lifetime test is usually carried out by accelerating the device aging at high brightness, and the lifetime at high brightness is obtained by fitting with an extended exponential decay brightness decay fitting formula. For example, the lifetime at 1000nit is denoted as T95@1000nit. The specific calculation formula is as follows:

[0141]

[0142] Among them, T95L The lifetime at low brightness, T95 H The measured lifetime at high brightness, L H When the device is accelerated to the highest brightness, L L is 1000 nit, A is the acceleration factor. In this experiment, the value of A is obtained as 1.7 by measuring the lifetimes of several groups of QLED devices at the rated brightness.

[0143] Table 2

[0144]

[0145] As can be seen from Table 2:

[0146] From Device Examples 1-3 and Device Comparative Example 1, it can be obtained that applying the composite material containing fluorinated lithium salt to the hole functional layer in the inorganic P-type semiconductor particles can effectively improve the external quantum efficiency and service life of the optoelectronic device and reduce the leakage current. This is because the fluorinated lithium salt can passivate the defects of the inorganic P-type semiconductor particles, improve the density of the hole functional layer, make the hole functional layer flatter, reduce the contact resistance between the hole functional layer and the light-emitting layer, thereby reducing the leakage current, and inhibiting the non-radiative relaxation of carriers at the interface between the hole functional layer and the light-emitting layer, improving the hole mobility, and further improving the external quantum efficiency and service life of the optoelectronic device;

[0147] From Device Examples 1, 4-7 and Device Comparative Example 1, it can be obtained that within the temperature and time ranges of the mixing reaction of the inorganic P-type semiconductor particles and the fluorinated lithium salt provided in this application, applying the composite material to the hole functional layer is beneficial to reducing the generation of leakage current in the optoelectronic device, improving the external quantum efficiency, and extending the service life. The fluorinated lithium salt can improve the performance of the optoelectronic device in many aspects, such as avoiding the aggregation of inorganic P-type semiconductor particles, promoting the effective transfer of holes between the hole functional layer and the light-emitting layer, reducing the defects of the composite material of the hole functional layer, etc.;

[0148] From Device Examples 1, 8-11 and Device Comparative Examples 1-3, it can be obtained that both organic fluorinated lithium salts and inorganic fluorinated lithium salts can effectively improve the performance of the optoelectronic device. This is because the improvement of the inorganic P-type semiconductor particles by the fluorinated lithium salt is mainly attributed to the conductivity of lithium ions and the electronegativity of fluorine atoms in the fluorinated lithium salt. Fluorine atoms can better fill the vacancies of oxygen atoms and tightly bind to the inorganic P-type semiconductor particles, maintaining and strengthening the stability of the composite material, thereby improving the performance of the optoelectronic device; in this application, after replacing the inorganic P-type semiconductor particles, applying the composite material to the hole functional layer can still reduce the leakage current, improve the external quantum efficiency and service life of the optoelectronic device.

[0149] The above has introduced in detail the composite material, its preparation method, optoelectronic device, and display device provided by the embodiments of the present application. Specific examples are used in this article to elaborate on the principle and implementation manner of the present application. The description of the above embodiments is only used to help understand the method and its core idea of the present application; at the same time, for those skilled in the art, according to the idea of the present application, there will be changes in the specific implementation manner and application scope. In summary, the content of this specification should not be construed as a limitation to the present application.

Claims

1. A composite material, characterized in that, It includes inorganic P-type semiconductor particles and fluorine-containing lithium salts.

2. The composite material according to claim 1, wherein in the composite material, the mass ratio of the inorganic P-type semiconductor particles to the fluorine-containing lithium salts is (10-20):1; and / or in the composite material, the inorganic P-type semiconductor particles contain metal cations, the fluorine-containing lithium salts contain fluoride ions, and the metal cations and the fluoride ions are connected by ionic bonds; and / or the composite material is composed of the inorganic P-type semiconductor particles and the fluorine-containing lithium salts.

3. The composite material according to claim 1, wherein the inorganic P-type semiconductor particles include one or more of first doped metal oxide particles, first undoped metal oxide particles, metal sulfides, metal selenides, and metal nitrides. The metal oxides in the first doped metal oxide particles and the metal oxides in the first undoped metal oxide particles independently include one or more of MoO3, WO3, NiO, CrO3, CuO, and V2O5. The doping elements in the first doped metal oxide particles include one or more of Mo, W, Ni, Cr, Cu, and V. The metal sulfides include one or more of CuS, MoS3, and WS3. The metal selenides include one or more of MoSe3 and WSe3. The metal nitrides include P-type gallium nitride; and / or the average particle size of the inorganic P-type semiconductor particles is 5nm - 10nm; and / or the fluorine-containing lithium salts include one or more of inorganic fluorine-containing lithium salts and organic fluorine-containing lithium salts.

4. The composite material according to claim 3, wherein the inorganic fluorine-containing lithium salts include one or more of lithium fluoride, fluorophosphate lithium salts, fluoroborate lithium salts, and fluorosilicate lithium salts; and / or the organic fluorine-containing lithium salts include one or more of lithium fluorosulfonylimide salts, lithium fluorooxalate borate salts, and lithium fluorosulfonate salts.

5. The composite material according to claim 4, wherein the fluorophosphate lithium salts include one or more of lithium hexafluorophosphate and lithium difluorophosphate; and / or the fluoroborate lithium salts include lithium tetrafluoroborate; and / or the fluorosilicate lithium salts include lithium hexafluorosilicate; and / or the lithium fluorosulfonylimide salts include one or more of lithium bis(trifluoromethylsulfonyl)imide, lithium trifluoromethanesulfonylimide, and lithium bis(fluorosulfonyl)imide; and / or the lithium borate salts include lithium difluorooxalate borate; and / or the lithium fluorosulfonate salts include one or more of lithium nonafluoro-1-butanesulfonate and lithium trifluoromethanesulfonate.

6. A method for preparing a composite material, characterized in that, It includes: providing a dispersion liquid of inorganic P-type semiconductor particles, wherein the dispersion liquid of inorganic P-type semiconductor particles includes inorganic P-type semiconductor particles; providing fluorine-containing lithium salts, and mixing the fluorine-containing lithium salts and the dispersion liquid of inorganic P-type semiconductor particles to obtain a composite material.

7. The preparation method according to claim 6, wherein The inorganic P-type semiconductor particles include one or more of first doped metal oxide particles, first undoped metal oxide particles, metal sulfides, metal selenides, and metal nitrides. The metal oxides in the first doped metal oxide particles and the metal oxides in the first undoped metal oxide particles independently include one or more of MoO3, WO3, NiO, CrO3, CuO, and V2O5. The doping elements in the first doped metal oxide particles include one or more of Mo, W, Ni, Cr, Cu, and V. The metal sulfides include one or more of CuS, MoS3, and WS3. The metal selenides include one or more of MoSe3 and WSe3. The metal nitrides include p-type gallium nitride; and / or The average particle size of the inorganic P-type semiconductor particles is 5 nm to 10 nm; and / or The fluorinated lithium salt includes one or more of inorganic fluorinated lithium salts and organic fluorinated lithium salts. Optionally, the inorganic fluorinated lithium salts include one or more of lithium fluoride, lithium fluorophosphate salts, lithium fluoroborate salts, and lithium fluorosilicate salts. The lithium fluorophosphate salts include one or more of lithium hexafluorophosphate and lithium difluorophosphate. The lithium fluoroborate salt includes lithium tetrafluoroborate. The lithium fluorosilicate salt includes lithium hexafluorosilicate. Optionally, the organic fluorinated lithium salts include one or more of lithium fluorosulfonylimide salts, lithium fluorooxalate borate salts, and lithium fluorosulfonate salts. The lithium fluorosulfonylimide salts include one or more of lithium bis(trifluoromethylsulfonyl)imide, lithium trifluoromethanesulfonylimide, and lithium bis(fluorosulfonyl)imide. The lithium fluorooxalate borate salt includes lithium difluorooxalate borate. The lithium fluorosulfonate salts include one or more of lithium nonafluoro-1-butanesulfonate and lithium trifluoromethanesulfonate.

8. The preparation method according to claim 6, wherein The mass ratio of the inorganic P-type semiconductor particles to the fluorinated lithium salt is (10 to 20):1; and / or In the inorganic P-type semiconductor particle dispersion, the mass concentration of the inorganic P-type semiconductor particles is 10 mg / mL to 40 mg / mL; and / or The inorganic P-type semiconductor particle dispersion further includes a solvent. The solvent includes one or more of chlorobenzene, diethylene glycol monobutyl ether, trimethoxybutanol, triethylene glycol monobutyl ether, diethylene glycol dimethyl ether, methanol, ethanol, propanol, butanol, ethylene glycol, isopropanol, glycerol, dimethyl sulfoxide, acetone, acetophenone, tetrahydrofuran, N,N-dimethylformamide, ethyl acetate, pyrrole, butyric acid, and cresol; and / or After the fluorinated lithium salt and the inorganic P-type semiconductor particle dispersion are mixed, heating is further included. The heating temperature is 150°C to 200°C. The heating time is 12 h to 18 h.

9. The preparation method according to claim 8, characterized in that, After the heating, separation and drying are further included. Optionally, the drying includes natural drying, heat drying, and vacuum drying. The heat drying temperature is 100°C to 120°C. The heat drying time is 5 h to 8 h.

10. An optoelectronic device, characterized in that, It includes an anode, a hole functional layer, an active layer, and a cathode which are stacked in sequence; the material of the hole functional layer includes the composite material described in any one of claims 1 to 5, or includes the composite material prepared by the preparation method described in any one of claims 6 to 9.

11. The optoelectronic device according to claim 10, wherein the anode and the cathode each independently include one or more of a metal, a carbon material, and a metal oxide; the metal includes one or more of Al, Ag, Cu, Mo, Au, Ba, Ca, Yb, and Mg; the carbon material includes one or more of graphite, carbon nanotubes, graphene, and carbon fiber; the metal oxide includes a metal oxide electrode or a composite electrode with a metal disposed between doped or undoped transparent metal oxides, the material of the metal oxide electrode includes one or more of ITO, FTO, ATO, AZO, GZO, IZO, MZO, MoO3, and AMO, and the composite electrode includes one or more of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, ZnS / Ag / ZnS, ZnS / Al / ZnS, TiO2 / Ag / TiO2, and TiO2 / Al / TiO2; and / or The material of the active layer includes a light-emitting material, and the light-emitting material includes one or more of an organic light-emitting material and a quantum dot light-emitting material; the organic light-emitting material is selected from one or more of 4,4'-bis(N-carbazolyl)-1,1'-biphenyl: tris[2-(p-tolyl)pyridineiridium(III)], 4,4',4”-tris(carbazol-9-yl)triphenylamine: tris[2-(p-tolyl)pyridineiridium], diarylanthracene derivatives, stilbene aromatic derivatives, pyrene derivatives, fluorene derivatives, TBPe fluorescent material, TTPX fluorescent material, TBRb fluorescent material, DBP fluorescent material, delayed fluorescence material, TTA material, TADF material, polymers containing B-N covalent bonds, HLCT material, and Exciplex light-emitting material; the quantum dot light-emitting material is selected from one or more of single-structure quantum dots, core-shell structure quantum dots, and perovskite-type inorganic particles; the materials of the single-structure quantum dots, the core materials of the core-shell structure quantum dots, and the shell materials of the core-shell structure quantum dots can be respectively selected from one or more of II-VI group compounds, IV-VI group compounds, III-V group compounds, and I-III-VI group compounds; the shell layer of the core-shell structure quantum dots is one or more layers; the II-VI group compounds are selected from one or more of CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe, and HgZnSTe; the IV-VI group compounds are selected from one or more of SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, and SnPbSTe;The III-V group compound is selected from one of GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb or Several; the I-III-VI group compound is selected from one or more of CuInS2, CuInSe2 and AgInS2; the quantum dots of the core-shell structure are selected from one or more of CdSe / CdSeS / CdS, InP / ZnSeS / ZnS, CdZnSe / ZnSe / ZnS, CdSeS / ZnSeS / ZnS, CdSe / ZnS, CdSe / ZnSe / ZnS, ZnSe / ZnS, ZnSeTe / ZnS, CdSe / CdZnSeS / ZnS and InP / ZnSe / ZnS; the perovskite inorganic particles are selected from one or more of doped or undoped inorganic perovskite semiconductors, or organic-inorganic hybrid perovskite semiconductors; the general structural formula of the inorganic perovskite semiconductor is AMX3, wherein A is Cs; + ion, M is a divalent metal cation selected from Pb 2+ Sn 2 + , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ One or more of, X is a halogen anion selected from Cl - Br - ,I - One or more of the following; the general structural formula of the organic-inorganic hybrid perovskite semiconductor is BMX3, wherein B is an organic amine cation selected from CH3(CH2) n-2 NH3 + or [NH3(CH2) n NH3] 2+ , where n≥2, M is a divalent metal cation selected from Pb 2+ 、Sn 2+ 、Cu 2+ 、Ni 2+ 、Cd 2+ 、Cr 2+ 、Mn 2+ 、Co 2+ 、Fe 2+ 、Ge 2+ 、Yb 2+ 、Eu 2+ one or more of, X is a halogen anion selected from Cl - 、Br - 、I - one or more of; and / or the optoelectronic device further includes an electron functional layer, and the electron functional layer is disposed between the active layer and the cathode; the material of the electron functional layer includes one or more of second doped metal oxide particles, second undoped metal oxide particles, IIB-VIA group inorganic particles, IIIA-VA group inorganic particles, and IB-IIIA-VIA group inorganic particles, the material of the second undoped metal oxide particles includes one or more of ZnO, TiO2, SnO2, ZrO2, and Ta2O5, the metal oxides in the second doped metal oxide particles include one or more of ZnO, TiO2, SnO2, ZrO2, Ta2O5, and Al2O3, the doping elements in the second doped metal oxide particles include one or more of Al, Mg, Li, Mn, Y, La, Cu, Ni, Zr, Ce, In, and Ga, the IIB-VIA group inorganic particles include one or more of ZnS, ZnSe, and CdS, the IIIA-VA group inorganic particles include one or more of InP and GaP, and the IB-IIIA-VIA group inorganic particles include one or more of CuInS and CuGaS.

12. A display device, characterized in that, It includes the optoelectronic device according to any one of claims 10 to 11.